2020
DOI: 10.2217/epi-2020-0193
|View full text |Cite
|
Sign up to set email alerts
|

Identification of tRNA-derived Fragments and their Potential Roles in Diabetic Cataract Rats

Abstract: Aim: To illustrate the expression profile of transfer RNA-derived fragments and reveal their putative role in the pathogenesis of diabetic cataract (DC) rats. Materials & methods: Small RNA sequencing was conducted in the lens epithelium of rats lens. The data were validated by quantitative real-time PCR, and bioinformatic analysis was performed to explore the roles of the fragments in DC pathogenesis. Results: A total of 213 differentially expressed tRNA-related fragments were identified, in which 111 wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 32 publications
0
9
0
Order By: Relevance
“…Nowadays, increasing studies have identified and emphasized the important role of tsRNAs in various diseases. 7,9,16,17 Therefore, we herein aimed to explore the expression pattern of tsRNAs, as well as the potential roles of candidate tsRNAs in the development of LN. Of note, our sequencing and qRT-PCR data showed that the expression levels and subtypes of tsRNAs were significantly altered in renal tissues of LN patients compared with the control.…”
Section: Discussionmentioning
confidence: 99%
“…Nowadays, increasing studies have identified and emphasized the important role of tsRNAs in various diseases. 7,9,16,17 Therefore, we herein aimed to explore the expression pattern of tsRNAs, as well as the potential roles of candidate tsRNAs in the development of LN. Of note, our sequencing and qRT-PCR data showed that the expression levels and subtypes of tsRNAs were significantly altered in renal tissues of LN patients compared with the control.…”
Section: Discussionmentioning
confidence: 99%
“…This research produced the first expression profile of tRFs/tiRs in DC rats and found that four types of tRFs/tiRs (tiRNA-Gly-GCC-002, tRF-Tyr-GTA-029, tRF-Thr-TGT-039 and tRF-Gln-CTG-043) are involved in the pathogenesis of DC. The identification of these tRFs/tiRs may provide a new perspective for further studies investigating the exact mechanism of DC [ 103 ].…”
Section: Trfs In Age-related Diseasesmentioning
confidence: 99%
“…They can be utilized as therapeutic targets and diagnostic biomarkers in tumor treatment ( Lee et al, 2009 ; Goodarzi et al, 2015 ; Olvedy et al, 2016 ; Huang et al, 2017 ; Zhu et al, 2020 ). Although tRFs in ophthalmic diseases have been widely researched, including diabetic cataracts and uveal melanoma ( Han et al, 2020 ; Londin et al, 2020 ), tRF expression and its potential roles in TAO have not yet been analyzed. We speculate that tRFs may be upregulated in TAO patients and are likely to have a regulatory effect on TAO pathogenesis.…”
Section: Introductionmentioning
confidence: 99%